RELATIONSHIP OF STRESS LEVEL WITH PRIMARY DYSMENORRHEA PAIN LEVEL IN FACULTY OF MEDICINE STUDENTS FROM WIDYA MANDALA CATHOLIC UNIVERSITY SURABAYA - Rissye Verina S. Jacub; Edith Maria Djaputra; Yudita Wulandari (FAKULTAS KEDOKTERAN UNIVERSITAS KATOLIK WIDYA MANDALA SURABAYA, 2023)
Background: Every month, women experience menstruation. Menstruation is the shedding of the endometrium, which causes periodic and cyclic bleeding. Primary dysmenorrhea is menstrual pain without underlying pathological conditions. The increased production of prostaglandins causes dysmenorrhea, and one of the causes of dysmenorrhea is stress. During this pandemic, many individuals feel bored and stressed, so researchers want to research the relationship between stress levels and primary dysmenorrhea pain levels.Objective: This research aimed to determine the relationship between stress levels with primary dysmenorrhea pain levels in the Faculty of Medicine students from Widya Mandala Catholic University.Method: This research used a cross-sectional method, and the samples used in this research were taken with simple random sampling. Respondents filled out the Kessler Psychological Distress Scale and Numerical Rating Scale questionnaires, distributed through Google Forms or online via Zoom application. Results: Respondents who experienced stress were 78.6%, and those who experienced dysmenorrhea pain were 93.4%. Most respondents experienced severe stress and severe dysmenorrhea pain, as much as 17.6%. Based on the Spearman correlation test, p-value = 0.001 and r = 0.270 indicates a significant positive relationship between stress levels and primary dysmenorrhea pain levels with a sufficient correlation between the two variables.Conclusion: There is a significant relationship between stress levels and primary dysmenorrhea pain levels in Faculty of Medicine students from Widya Mandala Catholic University.